2015
DOI: 10.2514/1.j053318
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Shape Optimization Investigations of the Common Research Model Wing Benchmark

Abstract: Despite considerable research on aerodynamic shape optimization, there is no standard benchmark problem allowing researchers to compare results. This work addresses this issue by solving a series of aerodynamic shape optimization problems based on the Common Research Model wing benchmark case defined by the Aerodynamic Design Optimization Discussion Group. The aerodynamic model solves the Reynolds-averaged Navier-Stokes equations with a Spalart-Allmaras turbulence model. A gradient-based optimization algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 263 publications
(175 citation statements)
references
References 44 publications
7
168
0
Order By: Relevance
“…Optimality refers to how closely the current point satisfies the first-order Karush-Kuhn-Tucker (KKT) conditions [29]. Approximately 2 orders of magnitude reduction in the optimality are achieved, which is similar to previous aerostructural [1] and aerodynamic optimizations [28]. A complete overview of optimized configuration with the initial design is shown in Figure 10.…”
Section: Optimization Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Optimality refers to how closely the current point satisfies the first-order Karush-Kuhn-Tucker (KKT) conditions [29]. Approximately 2 orders of magnitude reduction in the optimality are achieved, which is similar to previous aerostructural [1] and aerodynamic optimizations [28]. A complete overview of optimized configuration with the initial design is shown in Figure 10.…”
Section: Optimization Resultssupporting
confidence: 61%
“…The leading edge radius constraint ensure no reduction in leading edge radius, potentially causing reduction in the low-speed C Lmax performance. Previous aerodynamic optimizations have shown that single point optimized designs without this constraint produce very sharp leading edges in transonic flow [28]. The trailing edge constraints are used to ensure a manufacturable trailing edge that is not too thin.…”
Section: B Optimization Problem Descriptionmentioning
confidence: 99%
“…The computational cost of evaluating the partial derivatives of an objective or constraint function is insensitive to the number of design variables, requiring only one flow solution and one adjoint solution. This method becomes the most practical one for the design of complex aerodynamic configurations [56,57] because it can deal with the optimization problems with 100-1000 design variables [58,59] or even more. The drawback of a gradient-based method is that the solution optimality can be sensitive to the initial guesses, and it can become trapped into a local minimum [60].…”
mentioning
confidence: 99%
“…Along with the fluid flow model, the ASO framework requires a surface parameterization scheme which mathematically describes the aerodynamic shape being optimized by a series of design variables; changes in the design variables, which are made by a numerical optimization algorithm, result in changes in the aerodynamic surface. Numerous advanced optimizations using compressible computational fluid dynamics (CFD) as the aerodynamic model have previously been performed [3][4][5][6][7]. The authors have also presented work in this area, having developed a modularised, generic optimization tool, that is flow solver and mesh type independent, and applicable to any aerodynamic problem [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…For aerofoil optimization, it has been suggested that ASO problems exist that are unimodal [11] and multimodal [30,31], while the same is true of wings exhibiting unimodality [6] and multimodality [11]. Furthermore, recently, aerodynamic topology optimization results have suggested multimodality for a number of supersonic flow problems [32].…”
Section: Introductionmentioning
confidence: 99%